The dimensional validation of the Student Engagement Questionnaire (SEQ) with a Spanish university population. Students’ capabilities and the teaching-learning environment - Gargallo, Bernardo; Suárez-Rodríguez, Jesús M.; Almerich, Gonzalo; Verde, Irene; Cebrià i Iranzo, Maria Àngels (Anales de Psicología / Annals of Psychology, 2018)
In this work, the SEQ (Student Engagement Questionnaire - Kember & Leung, 2009) was validated with a Spanish sample. This instrument is designed to make a joint assessment of teaching-learning processes at university and to provide feedback to teachers and institutions to improve these processes. A sample of 805 subjects from three Valencian universities was used. The questionnaire assesses the capabilities of several students, and the teacher’s ability to design an adequate learning environment. Several versions have been developed until its dimensions (latent variables), and the relations between the involved variables, achieve high degree of stability. A confirmatory factor analysis corroborated the structure proposed by the authors and the relations between the involved variables. Hence the instrument seems suitable to be used in Spanish samples for the proposal it was designed for.